Avaliação da concordância diagnóstica entre a punção aspirativa de agulha fina transtorácica guiada por imagem e o exame histopatológico ou o bloco celular em pacientes do INCA, RJ entre 2000 e 2009 - Piragibe, Maria Midori Miura (2011)
Background: The tumors of the lung are the most frequent and one of de most deadly cancer types (Travis, 2004). The cytopathology plays an important role in the early diagnosis of lung cancer as a non-invasive or minimally invasive diagnostic technique (Erozan & Ramsy, 2009). Objective: To determine and report here an investigation of the utility of the immediate cytopathology (CITO I) when collecting specimens by tomography or fluoroscopy guided needle aspiration, and its degree of agreement with the correspondent histopathology, in order to conduct the patient to his first medical advice immediately after the diagnostic report based on the immediate cytopathology. Methods: Cytopathological reports were analysed from 880 patients for whom a final histopathologycal diagnosis could be made taken from among 3180 immediate cytology (CITO I) specimens between 2000 and 2009 at Instituto Nacional de Câncer, Rio de Janeiro, Brasil. In immediate cytopathology at our institute, a cytopathologist is present at the Computed Tomography (CT) or Fluoroscopy (FLC) room during the fine needle aspiration biopsy (FNAB) when the sample is collected and examined microscopically. A preliminary report is given orally at this time about the specimen adequacy. A code was used to analyse the cytopathological reports and registered in a database afterwards. We investigated whether the lesions were positive or negative, the tissue type (final diagnostic) and the diagnostic accuracy. Results: The 880 specimens cytological exams CITO I and CITO D had a Histopathology (HP) or cell block (CITO C) final diagnosis, and had a high correct diagnosis rate of 90,9% and 90,5% each one and a high sensitivity, specificity, positive and negative predictive values for non small cell lung carcinomas and small cell lung carcinomas. Conclusions: Because immediate cytology shows a high diagnostic accuracy, it can lead the patient to take an immediate therapy advice as well.